Improving Students' Independent Learning Outcomes and Science Through Discovery Learning - Matamay, Zubair; Sakung, Jamaludin M; Afadil, Afadil (FKIP Universitas Tadulako, 2023)
This study aims to improve student learning outcomes and independence through discovery learning in science subjects. Class action research methods. In the pre-action, there were 5 students (26.3%) who had fulfilled the KKM and there were 14 students (73.7%) who had not. In cycle I there were 10 students (52.7%) who fulfilled the KKM and 9 students (47.3%) who did not. Student independence was obtained by 12 students (63.16%) with sufficient criteria. and 7 students (36.84%) in less criteria. In cycle II there were 15 students (78.9%) who fulfilled the KKM and 4 students (21.1%) who had not, obtained student independence, namely there were 7 students (36.84%) with good criteria, there were 10 students (52.63 %) was sufficient, and there were 2 students (10.53%) lacking. The percentage of students who scored above the KKM in cycle I was 52.6% and cycle II was 78.9%, this shows that the discovery learning method was able to improve students' science learning outcomes.